Penggunaan Metode Outdoor Learning dalam Pembelajaran Tematik Peserta Didik Kelas III SDN 2 Kemuning Kota Banjarbaru: The Use of Outdoor Learning Methods in Thematic Learning for Students in Class III SDN 2 Kemuning Banjarbaru City - Faridah, Siti; Saputra, Ridho Indra; Tunnoor, Saidah; Mahrita, Mahrita; Ramadhani, M. Ihsan (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study aims to determine how the implementation of learning with outdoor learning methods, as well as the supporting and inhibiting factors experienced by teachers in applying this method in thematic learning in grade III SDN 2 Kemuning, Banjarbaru. The research used qualitative methods with data sources from students, teachers, the school environment, and related documents. Data collection techniques included observation, interviews, and documentation, and were tested for validity through triangulation of sources and techniques. Data analysis used the Miles and Huberman model: data reduction, data presentation, and conclusion drawing. The results showed that the outdoor learning method is very effective in increasing students' enthusiasm for learning. However, this method has supporting and inhibiting factors. In terms of learning, the advantages are that it is more applicable and inspiring because it provides real examples to students. Meanwhile, the obstacles include the need for more time in its implementation.